Optimalisasi Pendidikan Anak Dengan Ngaji Adventure: Belajar, Bermain, dan Berkarya - Mu’tafi, Ali; Syahrul Huda, Muhammad Reza; Soraya, Rani; Khabiburrochman, Adam; Agustina, Neli; Prihatin, Siti; Arifa, Ziida; Setiyo, Ulfan; Mahfiroh, Nailil; Mutmainah, Arifatul; Febriyanti, Febriyanti; Lestari, Simping Puji; Suroyo, Sigit Adhi; Anggun, Anggun; Triawan, Adis (Yayasan Inspirasi El Burhani, 2025)
Introduction: The role of religious education is vital in developing the character of children from a young age. However, conventional teaching techniques frequently do not effectively engage young learners in the process of reading the Qur’an at Taman Pendidikan Al-Qur’an (TPQ). Objective: This initiative seeks to boost children's interest and proficiency in Qur’anic reading at TPQ Al-Huda by introducing a novel method dubbed Ngaji Adventure: Learning, Playing, and Creating. Method: The approach applied in this initiative involves interactive education through multimedia resources, fun games like outdoor activities, and creative assignments utilizing recycled materials. The program was carried out in person over several weeks, involving 80 students from TPQ in various stimulating activities. Result: The findings indicated a heightened enthusiasm in children towards learning to read the Qur’an, along with enhancements in their social interaction and creativity. The children exhibited greater motivation to engage in Qur’anic educational activities, comprehend Islamic principles, and cultivate teamwork abilities through playful learning experiences Conclusion: The Ngaji Adventure initiative effectively increased children's engagement in Qur’anic education via a more enjoyable and impactful teaching style.